2014
DOI: 10.1155/2014/692061
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of LPS-Induced Inflammation Response in Microglia by AMPK Activation

Abstract: Adenosine 5′-monophosphate-activated protein kinase (AMPK) is a key regulator of cellular energy homeostasis via modulating metabolism of glucose, lipid, and protein. In addition to energy modulation, AMPK has been demonstrated to associate with several important cellular events including inflammation. The results showed that ENERGI-F704 identified from bamboo shoot extract was nontoxic in concentrations up to 80 μM and dose-dependently induced phosphorylation of AMPK (Thr-172) in microglia BV2 cells. Our find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…In fact, it has been demonstrated that in human vascular endothelial cells, the anti-inflammatory effect of adenine is mediated by its APRT-catalysed conversion into AMP and the subsequent activation of AMPK [96]. The same observation has been reported for murine microglial cells [97]. Adenine has also been demonstrated to cause cell cycle arrest and trigger autophagy in myelogenous leukaemia cells through the activation of AMPK.…”
Section: Adenine Phosphoribosyltransferasementioning
confidence: 59%
“…In fact, it has been demonstrated that in human vascular endothelial cells, the anti-inflammatory effect of adenine is mediated by its APRT-catalysed conversion into AMP and the subsequent activation of AMPK [96]. The same observation has been reported for murine microglial cells [97]. Adenine has also been demonstrated to cause cell cycle arrest and trigger autophagy in myelogenous leukaemia cells through the activation of AMPK.…”
Section: Adenine Phosphoribosyltransferasementioning
confidence: 59%
“…The majority of the published data on the bioenergetics of polarization states has been generated in peripheral immune cells (Biswas and Mantovani, ; O'Neill and Hardie, ; Pearce and Pearce, ) with only a few studies examining microglia (Moss and Bates, ; Chenais et al ., ; Bernhart et al ., ; Sohn et al ., ; Voloboueva et al ., ; Gimeno‐Bayon et al ., ). The majority of microglia studies were related to the generation of ROS (Innamorato et al ., ; Ferger et al ., ; Bordt and Polster, ; Chen et al ., ). As in macrophages, microglia in the surveillance state are likely to rely on oxidative phosphorylation metabolism (Cherry et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…They associate closely with the vasculature and play a key role in retinal vascular development [6,7], remodeling [8] and repair [9]. Activated microglia can cause tissue damage by the production of an array of cytotoxic factors including superoxide, nitric oxide [10,11], TNF-α [12,13], andIL1-β [14]. Microglia become activated in response to diverse stimuli, including neuronal damage, disease proteins and environmental toxins.…”
Section: Introductionmentioning
confidence: 99%